BIOETHANOL PRODUCTION FROM RICE STRAW BY SINGLE STEP FERMENTATION USING CO-CULTURE CLOSTRIDIUM THERMOPHILIC: A REVIEW - Wangiyana, I Gde Adi Suryawan (Jurnal Silva Samalas, 2018)
Bioethanol is a future renewable energy for gasoline substitution. Market need for bioethanol has been increased significantly in a decade. That will lead to unbalance between bioethanol supply and bioethanol demand if bioethanol production only come from starch and sugar source (first generation of bioethanol). Using lignocellulose waste (second generation of bioethanol) which abundand in Indonesia is one of good solution for this problem. Rice Straw production in Indonesia approximately 103.57 million ton in a year which make it is the most abundant lignocellulosa waste in this country. Optimizing bioethanol production using rice straw need two adjustment step. First step is adjustment in pre-treatment which important to breakdown insoluble lignin from the waste. Second step is selecting bioconvertion agent that has ability to carry single step fermentation process. Thermophilic clostridium is one of best bioconvertion agent for this process which has several advantage compare to others bioconvertion agent. This will lead to increase of bioethanol production to balance between bioethanol supplay and bioethanol demand.